Qawaid al-Tarjih fi al-Juz’i 30 fi Tafsir Ahkam Al-Qur’an - Maher Bin Ghazali (Studia Quranika, 2021)
This research examines the rules of preference (al-tarjih) in Ahkam al-Qur’an of Imam Ibn al-Arabi in its implementation in the Juz 30th of the Qur’an. Imam Ibn al-Arabi is one of the interpreter (al-mufassir) who proficiently employed the rules of preference in his interpretation of the Qur’an. It is due to that there are few mufassir to view this aspect, researcher investigates this issue using the inductive and analytical approach to convey rules of preference on which Ibn Arabi relied in his tafsir. Finally, researcher concludes that Ibn Arabi used various rules of preference including preferencing with Sunnah, include Atsar, language, Arabic Grammar, and the alphabets of the qur’an especially in Utsmany Mushaf.